Auranofin amplifies schisandrin A-induced apoptosis through ROS generation and inhibiting the PI3K/Akt pathway in hepatocellular carcinoma - Hyun Hwangbo; Seon Yeong Ji; Min Yeong Kim; Su Hyun Hong; Sung Ok Kim; Gi-Young Kim; Yung Hyun Choi (Asian Pacific Journal of Tropical Biomedicine, 2025)
Objective: To investigate the synergistic effects of auranofm and schisandrin A (SA) on cell proliferation inhibition and apoptosis induction in human hepatocellular carcinoma Hep3B cells. Methods: Cell viability was assessed using MTT to determine the synergistic effects of auranofin and SA. Three-dimensional (3D) culture models were used to evaluate the effects on spheroid structure and size. Apoptosis was analyzed by flow cytometry for sub-G1 populations, annexin V staining, and Western blotting for apoptotic markers. Reactive oxygen species (ROS) production was measured using DCF-DA staining. Results: Our results showed that combined treatment with auranofin and SA led to a significant reduction in cell viability compared with either compound alone, with isobologram analysis confirming their synergistic interactions. Under 3D culture conditions, auranofin and SA disrupted the compact structure of spheroids, leading to a loosened and disorganized morphology at the periphery, which appeared as an increase in spheroid size. Moreover, the induction of apoptosis by auranofin and SA was evidenced by elevated sub-G1 phase populations, increased annexin V-positive cells, and upregulation of apoptotic markers such as cleaved poly (ADP-ribose) polymerase 1 and cleaved caspase-3. Notably, auranofin combined with SA markedly enhanced ROS production, which was mitigated by the ROS scavenger N-acetylcysteine. Additionally, the phosphoinositide 3-kinase (PI3K)/Akt signaling pathway was downregulated in response to auranofin and SA treatment, and further apoptotic effects were observed following PI3K inhibition with LY294002. Conclusions: Auranofin combined with SA promotes apoptosis of hepatocellular carcinoma via ROS generation and inhibition of the PBK/Akt pathway.